2006
DOI: 10.1111/j.1398-9995.2006.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoter genetic variants of prostanoid DP receptor (PTGDR) gene in patients with asthma

Abstract: We identified a specific promoter variant of PTGDR that could be associated with asthma. This diplotype is a combination of the two highest transcriptional efficiency haplotypes, recently described. Our in vivo results would support for the first time what was demonstrated in vitro about high-transcriptional efficiency PTGDR haplotypes in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
38
1
17

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 20 publications
8
38
1
17
Order By: Relevance
“…24 The genetic predisposition of the familial clusters may present as a single phenomenon, that is, post-coital preterm delivery, or in association with environmental factors as well. 26 PTGDR gene variability has been shown to be associated with a predilection to smooth bronchial muscle excitability in response to exogenous factors in specific ethnic groups, 29,30 and hence, the virtually uniform ethnicity across the groups in our study supports the (possible) genetic and environmental basis for this model. Abbreviation: CI, confidence interval; IPB, idiopathic preterm birth; PCPB, post-coital preterm birth.…”
Section: Discussionsupporting
confidence: 69%
“…24 The genetic predisposition of the familial clusters may present as a single phenomenon, that is, post-coital preterm delivery, or in association with environmental factors as well. 26 PTGDR gene variability has been shown to be associated with a predilection to smooth bronchial muscle excitability in response to exogenous factors in specific ethnic groups, 29,30 and hence, the virtually uniform ethnicity across the groups in our study supports the (possible) genetic and environmental basis for this model. Abbreviation: CI, confidence interval; IPB, idiopathic preterm birth; PCPB, post-coital preterm birth.…”
Section: Discussionsupporting
confidence: 69%
“…The À441T/C polymorphism was associated with asthma development in the white population 11 but not in the Mexican population. 12 The À549T/C and À197T/C polymorphisms are associated with asthma development in the black 11 and Caucasian populations 13 , respectively. However, three SNPs were not significant in the Chinese population, as noted in our results.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of genetic variants in the promoter region of the PTGDR (À549, À441 and À197) have been reported for several ethnic groups. [11][12][13][14] These three polymorphisms were not always related to asthma, but they may have a role in controlling PTGDR expression. Therefore, the PTGDR may serve as a therapeutic target for asthma.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies indicated that the PTGDR variants in the promoter have functional impact on the expression of PTGDR. 10,11 The promoter SNP haplotypes (À549T/C, À441C/T, À197T/C) are shown to modify the PTGDR gene expression by altering the binding sites of the transcription factors, C/EBPb and members of the Sp and GATA families. 10 These transcription factors binding to the promoter are important for PTGDR transcription and the different SNPs change their binding efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Oguma et al 10 reported replicated associations of a PTGDR variant with asthma from six markers genotyped by using a Caucasian American population with 518 cases and 175 controls (P ¼ 0.04) and an African American population with 80 cases and 45 controls (P ¼ 0.01). Sanz et al 11 showed the association of a PTGDR variant with asthma (P ¼ 0.007) from three markers genotyped in a Caucasian Spanish population with 118 cases and 79 controls. In contrast, Noguchi et al 12 failed to demonstrate the associations of PTGDR variants with asthma in an asthma population of 144 Japanese families with 476 subjects; Tsai et al 13 did not observe the significant associations with asthma in three populations analyzed: Puerto Ricans, Mexicans and African Americans.…”
Section: Introductionmentioning
confidence: 99%